Hexavalent vaccines in infants: a systematic literature review and meta-analysis of the solicited local and systemic adverse reactions of two hexavalent vaccines. (4th March 2021) - Mukherjee, Piyali; Akpo, Essè Ifèbi Hervé; Kuznetsova, Anastasia; Knuf, Markus; Silfverdal, Sven-Arne; Kosalaraksa, Pope; Mihalyi, Attila
ABSTRACT: Introduction : The hexavalent vaccine DT3aP-HBV-IPV-Hib ( Infanrix hexa, GSK) was first licensed in Europe in 2000. DT2aP-HBV-IPV-Hib ( Hexyon/Hexacima/Hexaxim, Sanofi Pasteur), and DT5aP-HBV-IPV-Hib ( Vaxelis, MCM Vaccine Company) were licensed in the EU in 2013 and 2016, respectively, based largely on studies demonstrating non-inferiority to DT3aP-HBV-IPV-Hib for immunogenicity and comparable reactogenicity profiles. Methods : We conducted a systematic literature review looking for direct head-to-head trials comparing DT2aP-HBV-IPV-Hib and DT5aP-HBV-IPV-Hib with DT3aP-HBV-IPV-Hib. The incidence of solicited local and systemic reactions following primary series administration of DT3aP-HBV-IPV-Hib or DT2aP-HBV-IPV-Hib were meta-analyzed. Results : A total of 317 unique records were retrieved from the search; nine met the predefined inclusion criteria; seven reported studies comparing DT3aP-HBV-IPV-Hib and DT2aP-HBV-IPV-Hib. Six trials assessing outcomes of the primary vaccination series were identified. Odds ratios and 95% confidence intervals (OR; 95%CI) were computed for DT3aP-HBV-IPV-Hib, using DT2aP-HBV-IPV-Hib as reference, for redness (0.72; 0.63–0.83), pain (0.74; 0.62–0.89), swelling (0.86; 0.74–0.99) at injection site, fever (0.67; 0.54–0.83), persistent crying (0.72; 0.61–0.84), drowsiness (0.82; 0.71–0.94), irritability (0.82; 0.69–0.98), anorexia (0.83; 0.72–0.95), and vomiting (0.96; 0.83–1.11). Conclusion : ORs of analyzed local and systemic solicited adverse reactions after primary vaccination with DT3aP-HBV-IPV-Hib appear to be slightly lower than with DT2aP-HBV-IPV-Hib.